Tracing Homeness - Antoniou, Klitsa (My University, 2026)
Tracing Homeness, 5th International Exhibition of Sculptures and Installations, Open 2002 (Cyprus), Lido Venice, Text: Artemis Eleftheriadou, Stefan Tiron, Cyprus 2002